Check your vocabulary FCE plus : a vocabulary development workbook for students working towards the Cambridge First Certificate in English - Wyatt, Rawdon (A & C Black, 2007)
"Workbook provides exercises to help teach and build English vocabulary. Material covers general and topic-specific vocabulary, as well as grammar and use of English, comprehension, pronunciation and spelling"--P. [4] of cover